Mediation Using Covariance Based-Structural Equation Modeling (CB-SEM): The Why and How? - Rahman, Mohammad Mizanur; Adedeji, Samuel Babatunji; Bashir, Md Abdul; Islam, Jahirul; Reaz, Md; Khan, Arif Md (Asian Journal of Empirical Research, 2018)
This paper summaries and provides answers to some of the challenging issues in relation to mediation analysis. Specifically, emphasis was on four key burning aspects with reference to up-to-date literature on mediation analysis. For a better appreciation of the efforts put in here, scholars and practitioners, have some guidelines suggested to conceptualise, test and interpret a simple mediation model. Researchers have the benefits of updating their knowledge base from the current citations provided to carry out proper analysis based on informed decisions.